2019
DOI: 10.3390/en12234418
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of PWM-Induced Current Ripple in Subdivided Stator Windings Using Admittance Analysis

Abstract: Subdividing stator winding is a way to lower the DC link voltage value in electric drives and reduce the stress on motor insulation. Coupled windings sharing the same stator teeth are modelled in order to evaluate the link between voltages disparities and current ripple. This paper provides an assessment of current ripple rise in the subdivided windings compared to ordinary topologies through the use of a basic inductive model. A method for PWM-Induced current ripple and high-frequency loss estimation based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…An ordinary PWM technique is implemented [30]. Moreover, a common PWM carrier is used for the N sc elementary drives [12]. The key control difference between the two approaches lies in the coupling factor between sub-windings of the same phase, represented by double dotted lines in Fig.…”
Section: A Three-phase Motor Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…An ordinary PWM technique is implemented [30]. Moreover, a common PWM carrier is used for the N sc elementary drives [12]. The key control difference between the two approaches lies in the coupling factor between sub-windings of the same phase, represented by double dotted lines in Fig.…”
Section: A Three-phase Motor Segmentationmentioning
confidence: 99%
“…It opens up the possibility of dramatically lowering the drive voltage rating. However, it also induces high magnetic coupling between each winding sets [12] and may challenge the related torque and flux control structure. The key point of this article is to demonstrate that this issue can be addressed by an appropriate controller.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of the magnetic circuit and the conductors is different in those two bands. Even if the current magnitude is usually higher in the LF band than in the HF band, [6] has shown that the HF current ripple increase in stacked coils should also be taken into account. Thus two separate models are described, the LF model, based on an analytical method assesses the losses induced by a given current distribution between the stacked coils.…”
Section: Generic Problemmentioning
confidence: 99%
“…Each elementary coil being independently supplied, the whole structure presents new control degrees of freedom, these latter were investigated in the particular case of two coils with strong magnetic coupling [6]. A PWM-induced current ripple modelling method is detailed in [7] for conventional synchronous motor.…”
Section: Introductionmentioning
confidence: 99%
“…This compromise will guide the choice of the structure to be adopted for the control system. A first study [19,20] provides a better understanding of these phenomena.…”
Section: B) Difficulty Of Synchronizationmentioning
confidence: 99%